PENGARUH KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP MOTIVASI KERJA KARYAWAN - Khalidah, Nur Kamaliyah; Adi, Agung Nugroho (Jurnal Kewirausahaan dan Inovasi, 2022)
This research aims to identify the effect of financial compensation on employees work motivation and the effect of non-financial compensation on the said motivation. This explanatory research, which explains causal relationships between variables through hypothesis testing, was conducted at PT. Dawai Cita Semesta “Times Indonesia” of Malang city. Using saturated sampling or census, all 64 employees were selected as the sample. The testing instruments used in this study are validity test, reliability test, and classical assumption test. The results of the multiple regression analysis indicate that financial and non-financial compensation significantly influence the work motivation of employees at PT. Dawai Citra Semesta “Times Indonesia” of Malang city, East Java.